Association between lymphovascular invasion (LVI) and prognostic factors in breast cancer. - Kabir, Farzana; Tani, Sadia Afrin; Ullah, Md Amin; Hassan, ASM Farhad Ul; Islam, Mohammad Jayedul; Ansary, Janifa; Islam, Md Nazrul; Islam, Mohammad Jahirul (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: The presence of tumor cells within lymphatic or blood vessels in the surrounding tissue of a malignant tumor indicates the possibility of cancer spreading (metastasis) to other parts of the body. Lymphovascular invasion (LVI) is a significant pathogenic feature in invasive breast cancer that can provide valuable information about the tumor's aggressiveness and influence therapy options. Objective: To the association of LVI with prognostic factors in breast cancer. Methods: This cross-sectional study was conducted in the Department of Surgery, Sir Salimullah Medical College and Mitford Hospital, on 52 adult breast cancer patients who received Breast Conserving Surgery (BCS) or mastectomy. No patients with neoadjuvant therapy (recurring, breast cancer, metastases, or advanced breast cancer were excluded). Patients' demographic data, clinical data, and lab diagnoses were obtained. Histopathology and immunohistochemistry were performed on all samples. ER, PR, and Ki-67 were correlated with histological results. Pathologists diagnosed LVI in surgical resection tissue. All data were validated for consistency after collection. Data were analyzed using SPSS 12.0. A p value < 0.05 was considered statistically significant. Results: The presence of ER and PR was significantly higher in cases where LVI was negative. On the other hand, the presence of Ki-67 was significantly higher in cases where LVI was positive. It was observed that cases with LVI positive had higher stages of lymph nodes metastasis and tumor grading. It was also found that the Ductal type of breast cancer was significantly higher in cases where LVI was negative. Additionally, LVI positive case was found to be significantly higher among aged people. Conclusion: The presence of lymphovascular invasion has a negative association with ER, PR, and ductal type breast cancer and is positively associated with ki67, high grade, and greater lymph node metastasis. J Shaheed Suhrawardy Med Coll 2022; 14(2): 35-38